Bacterial diversity with emerging antimicrobial resistance of diabetic foot infection and their current detection techniques: A review - Alvi, Sayeed Akhtar (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2021.